Study of concentration and morphology of mechanoreceptors in the mucosa of uncinate process of the human nose - S. Abd Alrazaq , Adil (2011)
To study the mechanoreceptors in the human nasal mucosa and to compare the mean concentration of mechanoreceptors in the Uncinate Process mucosa in patients with and without nasal polyp.